RFID-Based Blood Bag Monitor Research - Zhou, Yucheng (Auckland University of Technology, 2015)
Medical errors occur during the blood transfusion are considered to be a major issue in the healthcare industry and may lead to a fatal consequence to the patient life. RFID technology is a feasible solution for this kind of issues. It provides both tracking and identification methods to ensure the quality of the blood products during the storage and transportation as well as the patient safety in the transfusion. In this research, we adopted the design science and experiment testing methodologies to create four different experiments in order to evaluate the performance of RFID technology in the blood bag storage phase. Some fundamental properties of the proposed RFID system has been tested in a simulated hospital blood bank situation, including the maximum detection range of tags and the maximum readable number of tags. Moreover, the best location for attaching the tag has been defined as well as the impact of the liquid on RFID has been measured. In addition, two different storage methods have been applied to the experiment so as to figure out a better one for the blood bag identification. The positive results of the experiment results indicate that RIFD technology can monitor the blood location during the fridge storage in the blood bank. Besides, some of the factors which may affect the performance of RFID system have been mentioned in this study. Also, a RFID-base fridge has been proposed and the next process in the blood transfusion has been designed in the future work.
Keywords: RFID; Blood transfusion